Avoiding Gaps in Romance: Evidence from Italian and French for a Structural Parsing Principle. (5th April 2021) - Konrad, Ingrid; Burattin, Massimo; Cecchetto, Carlo; Foppolo, Francesca; Staub, Adrian; Donati, Caterina
Abstract: Existing evidence suggests that the parser avoids positing a movement dependency if the grammar does not require doing so. By investigating the processing of two syntactic ambiguities that have not been the subject of processing studies before, we provide more conclusive evidence for this parsing bias in two Romance languages: French and Italian. In two acceptability‐judgment experiments and two self‐paced‐reading studies, we found that sentences that involved a filler–gap dependency (indirect questions in Italian and free relatives in French) were dispreferred compared to sentences involving the same lexical material but no filler–gap dependency (declarative complement clauses in both languages). Crucially, the filler–gap dependency was not dispreferred when there was no available competitor. We conclude by discussing the relevance of these results for syntactic theory, in particular for the questionable status of Merge over Move as a grammatical principle.